Extended plantar limb (modified) chevron osteotomy versus scarf osteotomy for hallux valgus correction: A randomised controlled trial. Issue 2 (June 2016) - Mahadevan, Devendra; Lines, Stephen; Hepple, Stephen; Winson, Ian; Harries, William
Highlights: The extended plantar limb chevron osteotomy was superior in correcting intermetatarsal angles. Both osteotomies produced comparable MOxFQ scores and patient satisfaction. Over 97% of patients reported good or moderate outcomes following hallux valgus surgery. The extended plantar limb chevron is a simpler osteotomy and is stable with a single screw fixation. Abstract: Background: The purpose of this RCT was to compare the extended plantar limb (modified) chevron osteotomy with the scarf osteotomy in correcting hallux valgus deformity and improving functional scores and patient satisfaction. Methods: Patients were randomly assigned and kept blind to surgical allocation. Cases requiring additional procedures including the Akin osteotomy were excluded. Outcomes were measured at 1 year following surgery. Results: 84 patients (109 feet) were analysed (60 modified chevron; 49 Scarf). The mean age was 50.7 years (75F: 9M). Post-operative intermetatarsal angle (IMA) was significantly lower in the modified chevron group (5.8° versus 6.9°, p  = 0.045). Hallux valgus angle and distal metatarsal articular angle were similar. The magnitude of IMA correction with the modified chevron was also significantly greater (9.1° versus 7.1°, p  = 0.007). Both osteotomies produced comparable MOxFQ scores and satisfaction ratings. Conclusion: The modified chevron was superior to the scarf osteotomy in correcting IMA in hallux valgus deformity.